The iron giant - Bird, Brad (Warner Home Video ; distributed in the Philippines by Warner Home Video (Phils)., 2000)
Hogarth Hughes just rescued an enormous robot that fell from the stars to Earth. Now young Hogarth has one very big friend and an even bigger problem: how do you keep a 50-foot-tall, steel-eating giant a secret?